Determinan Kejadian Stunting di UPT Puskesmas Sumbul Kecamatan Sumbul Kabupaten Dairi Tahun 2024 - Sihotang, Nola Winarta; Manurung, Kesaktian; Lia Rosa Veronika; Sembiring, Rinawati; Ginting, Daniel (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
malnutrition so that the child is too short for his age. Stunting has an impact on children's cognitive decline and productivity in the future. So far, addressing malnutrition has focused on babies from birth to five years old. In fact, the golden period is when the child is still in the womb until the age of two years. Therefore, a paradigm shift in handling malnutrition is needed. Therefore, the government is implementing the Acceleration of Nutrition Improvement Program with the First 1000 Days of Life Movement. SKI data for 2023, Dairi district is in second place with a figure of 32.6% of stunted toddlers out of 439 toddlers and based on the entry of toddler data on the e-PPGBM application in December 2024, the prevalence of stunted toddlers in the Sumbul Community Health Center, Sumbul District is around 13.98% or 258 toddlers. The incidence of stunting is influenced by several factors, namely maternal height, maternal education, compliance with taking blood supplement tablets and smoking. The aim of this research is to determine the determinants of stunting incidents at the Sumbul Community Health Center UPT, Sumbul District, Dairi Regency in 2024. This type of research is cross sectional with research methods. The population in this study were all mothers with toddlers. The number of samples in this study was 70 mothers. Based on the research results, it was found that there was a relationship between height and stunting (p-value=0.004), there was a relationship between maternal education and stunting (p-value=0.004), there was a relationship between adherence to taking blood supplement tablets and stunting (p-value=0.000) and there was a relationship between smoking and stunting (p-value=0.000). Increasing health promotion to the community about the importance of parenting patterns and fulfilling nutrition in the First 1000 Days of Life, starting from pregnant women until children are 2 years old, as well as outreach about the health of young women and prospective brides.